Journalism as an essential element in Woody Allen’s cinema - San José-De la Rosa, Cristina; Gil-Torres, Alicia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Allen's cinematography includes memorable journalistic episodes that deserve investigative attention to discover how the media set the pace of the plot in numerous scenes of the films of the last decades. In addition to masses of journalists behind a celebrity or at press conferences, there are also main characters such as the journalists from Scoop (2006) and A Rainy Day in New York (2019). This work is inspired by methods that seek to decompose the character, for which the lines of the authors Casetti and Di Chio have been chosen. In the 15 films analyzed, it is detected that journalistic moments appear in 80%.